2014
DOI: 10.1111/1744-7917.12106
|View full text |Cite
|
Sign up to set email alerts
|

Over‐transcription of genes in a parathion‐resistant strain of mosquito Culex pipiens quinquefasciatus

Abstract: Insecticide resistance is an evolutionary adaptation that develops quite quickly in mosquitoes because of the high selection pressure of chemical insecticides, rapid generation time and large population size. Identification of genes associated with insecticide resistance is fundamental to understand the complex processes responsible for resistance. We compared the gene transcriptional profiles of parathion-resistant and -susceptible Culex pipiens quinquefasciatus using a combination of suppression subtractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 37 publications
(43 reference statements)
1
19
1
Order By: Relevance
“…Chymotrypsin functions in the digestive systems of many organisms, including insects, and aids the metabolism of endogenous and xenobiotic peptide compounds. It is hypothesized that chymotrypsin can sequester or degrade pesticides (Wang et al ., ); however, its down‐regulation in response to sublethal concentrations of different pesticides in the present study and protoxins in the previous study of Vellichirammal et al () might indicate its lesser role in xenobiotic detoxification. However, the responses are mainly dependent on the life stage exposed, the duration of exposure and the concentrations of pesticides used, and therefore further studies are required to adequately clarify its role in detoxification.…”
Section: Discussioncontrasting
confidence: 69%
“…Chymotrypsin functions in the digestive systems of many organisms, including insects, and aids the metabolism of endogenous and xenobiotic peptide compounds. It is hypothesized that chymotrypsin can sequester or degrade pesticides (Wang et al ., ); however, its down‐regulation in response to sublethal concentrations of different pesticides in the present study and protoxins in the previous study of Vellichirammal et al () might indicate its lesser role in xenobiotic detoxification. However, the responses are mainly dependent on the life stage exposed, the duration of exposure and the concentrations of pesticides used, and therefore further studies are required to adequately clarify its role in detoxification.…”
Section: Discussioncontrasting
confidence: 69%
“…Such combined approaches have revealed that several genes are highly overexpressed in resistant mosquitoes (Hemingway, 1985;Grigoraki et al, 2016;Riveron et al, 2013;Strode et al, 2008). Microarray and transcriptome analysis have revealed the involvement of new candidate genes, which are involved in insecticide resistance of mosquitoes (David et al, 2005;Wang et al, 2015). Silencing of genes through RNA interference (RNAi) in insects has been a powerful tool to study mortality, growth and insecticide susceptibility in the recent past (Killiny et al, 2014).…”
Section: Recent Approaches and Concernsmentioning
confidence: 99%
“…quinquefasciatus mosquitoes are able to survive in polluted waters where there are no natural predators, which leads to excessive growth of the population [12]. This phenomena may be due to phenotypic plasticity and might have a role in environmental adaptation and insecticide resistance with implications that made chemical interventions no longer effective for the control of mosquito populations [13][14][15][16][17][18][19][20][21][22]. Therefore, a better knowledge of the genetic structure of insect populations is required for the development of effective strategies for vector control.…”
Section: Introductionmentioning
confidence: 99%